2014
DOI: 10.3109/15622975.2014.885659
|View full text |Cite
|
Sign up to set email alerts
|

A review of fMRI studies during visual emotive processing in major depressive disorder

Abstract: In general, depressed patients have increased activation to emotive, especially negative, visual stimuli in regions involved in affective processing, with the exception of certain PFC regions; this pattern tends to normalize with treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 104 publications
8
82
0
2
Order By: Relevance
“…Elevated activity in the PFC and the ACC has been shown during non-affective cognitive tasks in MDD patients as compared to controls using fMRI (Kerestes et al, 2014). Emotional cognition, in contrast, seems to also involve area of the amygdala and the hippocampus which show increased activation with emotive negative visual challenges processing; effects which are typically reversed by antidepressants (Jaworska et al, 2014;Kerestes et al, 2014). In addition poor performance on hippocampal-related memory tasks in MDD has been reported to precede any changes in hippocampal volume (Malykhin and Coupland, 2015).…”
Section: Neurodegenerative Changesmentioning
confidence: 96%
“…Elevated activity in the PFC and the ACC has been shown during non-affective cognitive tasks in MDD patients as compared to controls using fMRI (Kerestes et al, 2014). Emotional cognition, in contrast, seems to also involve area of the amygdala and the hippocampus which show increased activation with emotive negative visual challenges processing; effects which are typically reversed by antidepressants (Jaworska et al, 2014;Kerestes et al, 2014). In addition poor performance on hippocampal-related memory tasks in MDD has been reported to precede any changes in hippocampal volume (Malykhin and Coupland, 2015).…”
Section: Neurodegenerative Changesmentioning
confidence: 96%
“…A number of fMRI studies have reported amygdala hyper-reactivity in response to negative emotional faces in MDD overall relative to controls under both supraliminal (Peluso et al, 2009;Surguladze et al, 2005;Fu et al, 2004;Zhong et al, 2011) and subliminal (Sheline et al, 2001;Victor et al, 2010;Stuhrmann et al, 2012;Suslow et al, 2010) (for meta-analysis see the study by Hamilton et al (2012); for review see the studies by Browning et al (2010);Jaworska et al (2014)). These studies have typically reported on medicated patients, who by virtue of still meeting criteria for the disorder while on medication are likely non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…To identify potential biomarkers of a depressive-like state in mice, we conducted a genome-wide transcriptome analysis on all RNA samples extracted from blood and the DG and ACC regions of the brain, both of which play major roles in emotion processing and are known to be altered in affective disorders (Jaworska et al, 2015). Processing of the raw data resulted in 17,368 analyzable probes for blood and 33,264 probes for each brain region.…”
Section: Blood Transcriptional Profiles Reflect Behavioral Variationsmentioning
confidence: 99%
“…We utilized the unpredictable chronic mild stress (UCMS) model, which has contributed to the elucidation of the pathophysiological mechanisms of depression such as decreased neurogenesis, hypothalamic-pituitary-adrenal (HPA) axis alterations and maladaptive changes in amygdala (Surget et al, 2008;Sibille et al, 2009;Nollet et al, 2013). We aimed to correlate depressive-like behavior induced by UCMS protocol and fluoxetine-induced recovery with transcriptional signatures from whole blood as well as the hippocampus and the anterior cingulate cortex (ACC), two brain regions involved in mood regulation in which dysfunction has been reported in MDD (Rive et al, 2013;Jaworska et al, 2015;Wise et al, 2016). Since the hippocampus is known to have large variations in gene expression, we focused on the dentate gyrus (DG) where adult neurogenesis has been described and linked to psychiatric illness (Kohen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%